Potential exports and nontariff barriers to trade Bhutan national study. (Potential exports and nontariff barriers to trade., 2021)
It focuses on sanitary and phytosanitary measures and technical barriers to trade, and on export products that have the potential to increase their market share in Bangladesh, India, Maldives, Nepal, and Sri Lanka. It considers options including legal reforms, the upgrade of quality standards and laboratory equipment, and institution building of accrediting bodies and conformity assessment bodies. Practical recommendations suggest ways forward for both the public and private sectors.